PENERAPAN MODEL ILL STRUCTURED COOPERATIVE PROBLEM SOLVING (ICPS) UNTUK MENINGKATKAN METAKOGNISI SISWA (Journal of Innovative Science Education, 2015)
Pembelajaran IPA di MTsN Sumenep yang memberdayakan metakokgnisi belum dilakukan secara sengaja serta belum adanya perangkat pembelajaran yang berorientasi pada peningkatan metakognisi. Pembelajaran CPS merupakan model pembelajaran yang dapat mengembangkan metakognisi dengan membiasakan peserta didik memecahkan masalah. Karakteristik model ICPS yang dikembangkan dengan ill structured problem yaitu adanya masalah yang bersifat ill structured problem yang harus dipecahkan peserta didik dan pelajaran berpusat pada peserta didik secara mandiri dalam kelompok. Keefektifan perangkat pembelajaran berdasarkan tes pemahaman konsep mengalami peningkatan rata-rata N-gain kelas eksperimen dengan kategori tinggi. Keterlaksanaan pembelajaran pada kelas eksperimen pada pertemuan pertama sampai ke lima telah dilakukan dengan kategori baik. Guru dan peserta didik memberikan respon positif terhadap perangkat pembelajaran yang diterapkan di dalam kelas. Science teaching equipments at Madrasah Tsanawiyah Negeri (MTsN) Sumenep, grounded in metacognition  have not yet been deliverately developed because of the lack of learning equipments oriented in metacognition. CPS as a teaching models that can develop metacognition can be used to familiarize students to solve problems. The characteristics of the CPS model are developed through problems that are ill structured, which are problems that must be solved by students and study material that are centered around students and must be completed individually and in a group.The results showed that teaching equipments were valid. The effectiveness of teaching equipments based on concept understanding was increased by an average N-gain of experimental class which are respectively classified as high category. The feasibility of the teaching equipments at the treated (experiment) class from the first until seventh meeting was in good category. The teacher and students responded positively of the teaching equipments in the classroom.